The Influence of Ease of Use, Cashback and Discounts, and User Experience on Consumer Behavior in Using E-Wallets: A Study in Bengkulu City - Elwis, Mutiara; Hayadi, Ilsya (Universitas Muhammadiyah Pontianak, 2025)
This study aims to examine the influence of ease of use, cashback and discounts, and user experience on the consumer behavior of e-wallet users in Bengkulu City. A quantitative approach was used with a survey method. Primary data were collected through a questionnaire distributed to 150 active e-wallet users in Bengkulu City, using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4. The findings reveal that promotional strategies such as cashback and discounts have a positive influence on consumer behavior. However, ease of use and user experience do not have a significant positive impact. These results suggest that cashback and discount strategies play a more dominant role in influencing consumer behavior compared to ease of use and user experience.